Treatment of Schizophrenia, the manic-depressive psychosis and alcoholism with chlorpromazine - Querol L., Marino (1957)
The use of any treatment involves a philosophical attitude about the cause of the disease to be cured. Psychiatric treatments are no exception to this rule. Indeed, the therapeutic nihilism corresponds to the time when the mental patient was considered a possessed or alienated. In the mid and late nineteenth century the foundations of psychiatry sat organism and consequently more diverse methods of treatment and consistent with course organic cause of the disease were used; in an effort to find an effective remedy for mental disorders, researchers have tried countless substances, drugs, hormones, surgical techniques and the most varied therapeutic methods with which we have tried to achieve healing effects.